Visualizing sulfur with X-rays: From molecules to tissues. (3rd July 2019) - George, Graham N.; Pickering, Ingrid J.; Cotelesage, Julien J. H.; Vogt, Linda I.; Dolgova, Natalia V.; Regnier, Nathan; Sokaras, Dimosthenis; Kroll, Thomas; Sneeden, Eileen Y.; Hackett, Mark J.; Goto, Kei; Block, Eric
Abstract: Sulfur is sometimes called a spectroscopically silent element because there are so few tools for probing its chemistry. This paper will review how sulfur K-edge X-ray absorption spectroscopy and related methods can be used to overcome this limitation, using examples from the authors' research. X-rays from synchrotron radiation sources provide the means to study essentially any element in a variety of systems, ranging from pure compounds, to complex mixtures and even structured systems such as biological tissues. We show that sulfur K-edge X-ray absorption spectroscopy provides an important spectroscopic probe of sulfur chemistry in a range of systems, including those containing reactive species. Using a micro-focused X-ray beam, chemically-dependent X-ray fluorescence imaging can be used to image different sulfur species at a variety of spatial resolutions from microscopic to macroscopic. Increased sensitivity and deeper insights into electronic structure will be available in future studies using a suite of methods that are collectively known as advanced X-ray spectroscopy. Graphical abstract: UF0001